NUTRIENTS CHANGES DURING OFF-SEASON FLOWERING IN CUSTARD APPLE (ANNONA SQUAMOSA L.) CV. BALANAGAR INDUCED BY PRUNING AND DEFOLIATION - G. M. VINAY,; R. CHITHIRAICHELVAN,; G. K. HALESH, (The Bioscan, 2015)
A field experiment was conducted during 2013-2014 to study the nutrients changes in the leaf of custard apple cv. Balanagar, under different pruning with defoliation treatments during off-season flowering. Nitrogen, Phos- phorus, Potassium, Calcium, Magnesium, Sulphur, Zinc, Manganese, Iron and Cupper concentrations were monitored before treatment application and after treatments application. All nutrient levels in leaves of Custard apple cv. Balanagar more in the treated trees than the before application of the treatments; N-2.65% (T 6 ), P-0.29% (T 7 ), K-2.33% (T 2 ), Mg-0.68% (T 7 ), S-0.59% (T 7 ), Zn-9.23ppm (T 9 ), Mn-75.85ppm (T 9 ), Cu-28.55ppm (T 7 ) but calcium 5.08% (T 1 )and iron 335.33ppm (T 1 ) were more in the control tress than the before application and after application of the treatment. Such nutrients changes within the Balanagar leaves may have resulted in greater vegetative growth, flowering and fruiting, giving rise to off-season flowering with yield of 10.33 kg per plant in the treatment of 25 per cent pruning + Urea 5 per cent than the other treatments.